2009
DOI: 10.1634/theoncologist.2009-0109
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal VEGF Inhibition Using Bevacizumab: A Potential Approach for the Symptomatic Treatment of Malignant Ascites?

Abstract: Despite overall improvements in oncological care in the palliative setting, symptomatic malignant ascites remains a severe clinical problem. This form of effusion is known to be widely resistant to established modes of systemic therapy. Accordingly, frequent paracentesis often represents the only effective way for symptom relief in patients with advanced cancer. This invasive mode of therapy, however, is often very burdensome for the patient who is already severely distressed by the underlying malignancy. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
85
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 100 publications
(117 reference statements)
2
85
0
Order By: Relevance
“…agents are readily absorbed by the peritoneal tumour tissue. Thirdly, this route was likewise successfully used in most pre-clinical animal models [7,14] The overall median ParFS, based on observed events in all patients, was 13 d for the whole study population (95% CI: 10e15 d). This is in accordance with the assumed median of 14 d, which formed the basis for the statistical design calculation of the trial.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…agents are readily absorbed by the peritoneal tumour tissue. Thirdly, this route was likewise successfully used in most pre-clinical animal models [7,14] The overall median ParFS, based on observed events in all patients, was 13 d for the whole study population (95% CI: 10e15 d). This is in accordance with the assumed median of 14 d, which formed the basis for the statistical design calculation of the trial.…”
Section: Discussionmentioning
confidence: 97%
“…), in patients with ascites secondary to a variety of solid tumours, predominantly ovarian cancer. However, the sample sizes were rather small, ranging from 1e9 patients [7,12]. For the largest series, published in abstract form, ElShami et al reported resolution or at least distinctly delayed reaccumulation of ascites in all of the nine patients enrolled, after only one i.p.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations